Synchronous Primary Carcinoma in 5 Different Organs of a Female Genital Tract: an Unusual Case and Review of the Literature. Issue 4 (1st April 2009) - Atasever, Melahat; Yilmaz, Bulent; Dilek, Gulay; Akcay, Eda Yilmaz; Kelekci, Sefa
Abstract : The occurrence of double simultaneous primary cancers of the female reproductive tract is a common event. However, the occurrence of synchronous primary quadruple gynecologic malignancies is extremely rare. In this report, the clinical and pathological findings of a 35-year-old female patient with synchronous primary gynecologic cancers regarding papillary serous carcinoma of the left ovary, microinvasive carcinoma in situ of the left and right uterine tubes, endometrial intraepithelial carcinoma of the endometrium, and endocervical carcinoma in situ of the uterine cervix were presented. To our knowledge, the patient presented is the first case in aspect of accompanying ovarian papillary serous carcinoma to bilateral tubal microinvasive carcinoma in situ, endometrial intraepithelial carcinoma, and endocervical carcinoma in situ of the uterine cervix.